2018
DOI: 10.3174/ajnr.a5588
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Malformations of the Middle and Inner Ear in 22q11.2 Deletion Syndrome: Case Series and Literature Review

Abstract: Middle and inner ear abnormalities were frequently encountered in our cohort, including malformations of the lateral semicircular canal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 49 publications
2
19
3
Order By: Relevance
“…A pathologically hyperdensity was also found in the manubrium of the malleus in 2 ears. Abnormal malleus, incus and anomalous stapes orientation were also described [71,74]. The Authors speculate against the possible "tympanosclerotic" origin of these dense ossicles, given that it was also encountered in newborns with no history of otitis media and in patients with no signs of reduced mobility of the ossicular chain at audiogram [74].…”
Section: Petrous Bone Imaging Findingsmentioning
confidence: 95%
See 4 more Smart Citations
“…A pathologically hyperdensity was also found in the manubrium of the malleus in 2 ears. Abnormal malleus, incus and anomalous stapes orientation were also described [71,74]. The Authors speculate against the possible "tympanosclerotic" origin of these dense ossicles, given that it was also encountered in newborns with no history of otitis media and in patients with no signs of reduced mobility of the ossicular chain at audiogram [74].…”
Section: Petrous Bone Imaging Findingsmentioning
confidence: 95%
“…Inner ear: In one study, 33 % of the patients had a malformed lateral SCC and 29 % showed a single cavity between the vestibule and lateral SCC [74] (Fig. 10C).…”
Section: Petrous Bone Imaging Findingsmentioning
confidence: 97%
See 3 more Smart Citations